2015
DOI: 10.1016/j.bone.2015.02.004
|View full text |Cite
|
Sign up to set email alerts
|

The decrease in silicon concentration of the connective tissues with age in rats is a marker of connective tissue turnover

Abstract: Silicon may be important for bone and connective tissue health. Higher concentrations of silicon are suggested to be associated with bone and the connective tissues, compared with the non-connective soft tissues. Moreover, in connective tissues it has been suggested that silicon levels may decrease with age based upon analyses of human aorta. These claims, however, have not been tested under controlled conditions. Here connective and non-connective tissues were collected and analysed for silicon levels from fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 52 publications
1
30
0
Order By: Relevance
“…In contrast, disorganized fibrous tissue infiltrated the DCB scaffold (stained red). These results are also supported by the literature in regard to the active involvement of Si ions in matrix synthesis, maturation, and turnover to maintain matrix stabilization . Therefore, these nSC composites indeed provide a natural bone ECM‐mimicking niche for endogenous cells to attach, grow, and differentiate into mature bone tissue and thus present a superior capacity for enhanced bone regeneration.…”
supporting
confidence: 80%
“…In contrast, disorganized fibrous tissue infiltrated the DCB scaffold (stained red). These results are also supported by the literature in regard to the active involvement of Si ions in matrix synthesis, maturation, and turnover to maintain matrix stabilization . Therefore, these nSC composites indeed provide a natural bone ECM‐mimicking niche for endogenous cells to attach, grow, and differentiate into mature bone tissue and thus present a superior capacity for enhanced bone regeneration.…”
supporting
confidence: 80%
“…Indeed, Zhang et al recently reported elevated serum homocysteine levels in patients with severe OA compared to those with mild OA or healthy controls [29]. Secondly, although the exact role of silicon in bone and connective tissue health remains unclear, its involvement in collagen synthesis and/or stabilisation was recently put forward by Jugdaohsingh et al [30]. In the present study, the lack of correlation between the change in serum silicon and clinical parameters in men taking ch-OSA, suggests that the effect of ch-OSA cannot be explained as an effect of silicon only.…”
Section: Discussionmentioning
confidence: 99%
“…Silicon is a microelement whose role and essentiality for the human organism remains unclear [25]. However, in view of the available research data its connection with the functioning of connective tissues seems to be unquestionable [26,27]. An association has been found between dietary silicon and bone condition in humans [28].…”
Section: Introductionmentioning
confidence: 99%